Jack Reacher : One Shot - Book 9 - Child, Lee (New York : Dell, 2009)
Ex-military investigator Jack Reacher is called in by James Barr, a man accused of a lethal sniper attack that leaves five people dead, and teams up with a young defense attorney to find an unseen enemy who is manipulating events.
Keywords: Reacher, Jack -- (Fictitious character); Fiction; Military police; Fiction; Serial murders -- Fiction; Snipers -- Fiction; Middle West -- Fiction; Detective and mystery fiction